2023
DOI: 10.15294/biosaintifika.v15i2.46501
|View full text |Cite
|
Sign up to set email alerts
|

Callogenesis of Dayak Onion (Eleutherine palmifolia) Bulb in response of Picloram, 2,4-D, and Kinetin

Noor Aini Habibah,
Ananda Lutfiah,
Alin Liana
et al.

Abstract: Dayak onion contains bioactive compounds that are traditionally used for medicine. The production of bioactive compounds can be increased through callus culture. This study aims to analyze the effect of the combination of plant growth regulator on the growth of Dayak bulb callus. The design of this study used a completely randomized factorial design with 2 factors. The first factor is the concentration of auxin. While the second factor is the concentration of kinetin. The parameters observed include the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The addition of kinetin at various concentrations caused callus texture to become compact and intermediate. These results showed that different types and concentrations of growth regulators http://journal.uinsgd.ac.id/index.php/biodjati could cause variation in callus texture, as reported by Habibah et al(2023). However, Sari et al(2018) stated that increasing the concentration of 2,4-D and kinetin produced friable callus.…”
Section: Callus Morphologymentioning
confidence: 65%
See 3 more Smart Citations
“…The addition of kinetin at various concentrations caused callus texture to become compact and intermediate. These results showed that different types and concentrations of growth regulators http://journal.uinsgd.ac.id/index.php/biodjati could cause variation in callus texture, as reported by Habibah et al(2023). However, Sari et al(2018) stated that increasing the concentration of 2,4-D and kinetin produced friable callus.…”
Section: Callus Morphologymentioning
confidence: 65%
“…These results showed that the addition of 2,4-D and kinetin at higher concentrations of 2 mg/L caused callus to turn brownish-yellow. Similarly, (Habibah et al(2023) and Harahap et al(2020) reported brownish-white to yellow callus from MS media supplemented with the increasing concentration of 2,4-D and kinetin. Mahadi and Sari (2016) stated that the addition of cytokinin into MS media played an important role in the transportation of nutrients, which was capable of causing the lignification process to produce a harder and more compact texture.…”
Section: Callus Morphologymentioning
confidence: 78%
See 2 more Smart Citations
“…The purpose of callus production in this research is to produce secondary metabolite compounds, while the ideal callus for secondary metabolite production is callus with a compact structure. According to Habibah et al (2023), the compact callus texture is characterized by a dense arrangement of cells, the form of a solid bulge, and less water content, which contributes to its firm structure. The difference in callus texture has a different ability to produce metabolite compounds.…”
Section: Results and Discussion Callus Morphology Of Talinum Paniculatummentioning
confidence: 99%